2022
DOI: 10.1002/nau.24889
|View full text |Cite|
|
Sign up to set email alerts
|

An anatomical pathogenesis of lower urinary tract definitions from the 2002 ICS report symptoms, conditions, syndromes, urodynamics

Abstract: Aim To present an anatomical pathogenesis parallel with the 2002 International Continence Society Lower Urinary Tract (LUTS) definitions standardization Report 2002. Methods Each LUTS section is discussed using the same numbers as the Report. Results Normal function Bladder control is binary, with two reflexes alternating, either closure (dominant) or open (micturition), with the same cortical and peripheral components: three directional muscle forces contracting against pubourethral (PUL) and uterosacral (USL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In addition, the point of C during straining also had a more ventral location in patients with vLUTS than in those without vLUTS, which was associated with longer iUSL and iCL during straining. Consequently, C, which is thought to be a keystone of the pelvic organs, 15,16 and with PUVA >140 (no marked urethral kinking) when BN descended more than 2 cm. 17 They concluded that BOO caused urethral kinking in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the point of C during straining also had a more ventral location in patients with vLUTS than in those without vLUTS, which was associated with longer iUSL and iCL during straining. Consequently, C, which is thought to be a keystone of the pelvic organs, 15,16 and with PUVA >140 (no marked urethral kinking) when BN descended more than 2 cm. 17 They concluded that BOO caused urethral kinking in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the point of C during straining also had a more ventral location in patients with vLUTS than in those without vLUTS, which was associated with longer iUSL and iCL during straining. Consequently, C, which is thought to be a keystone of the pelvic organs, 15,16 might prevent BN and B from being displaced more dorsally during straining and might even play some role in more ventral BN movement during straining. These positions/movements might be partially associated with a more ventral position of AR in patients with vLUTS than in those without vLUTS because the vertical length of the urogenital hiatus (H‐line) was moderately correlated to ARx during straining ( r = 0.511, p < .0001), which suggested that subtle differences in pelvic floor muscle impairment may contribute to the presence or absence of vLUTS.…”
Section: Discussionmentioning
confidence: 99%
“…In the article by Petros et al, 1 Figure 8 and its caption contained error. The corrected Figure and caption appear below:…”
Section: Figurementioning
confidence: 99%
“…What is meant by “urethral failure”? If “urethral failure” means the detrimental effect on urethral resistance to flow, Figure 5, by muscle or ligament weakness, 9 then the ITS, “three theory paradigm” and “urethral failure” proposals may (possibly) all be “on the same page,” if the “urethral failure” concept accords with ITS for function 9,11 and dysfunction 52 …”
Section: Rebuttalmentioning
confidence: 99%